Ontem, confrontos e conflitos : hoje, monumentos : o levante dos posseiros de 1957 e seus monumentos na fronteira sudoeste do Paraná - Silva, Moacir Motta da (2014)
This research, which deals with the conflicts and clashes in the west of Paraná border in a review noting the different versions built about Squatters Revolt of 1957 in the border region with the cultural clash of migrants and mestizos during the March to the West established the President and Vargas, this approach submit the monuments on the border. For with the outcome of the conflict it created an official memorial to the conflict turned into a historic symbol of the Southwestern region of Paraná, we intend to submit the events related crimes Squatters Revolt of 1957 especially on the conflicts that occurred in the border , seeking to understand the conflicts between settlers and territorial gunmen occurred in this group. Thus we intend to demonstrate that conflicts occurred in the majority in this region also shows the installation of the Registry of Real Estate was not brought up in obscurity for the registration of the deed in favor of CITLA, but was installed according to the region that had been installed. Analyzing the different versions, ie, the narratives of the time, the official memory and individual officers memories built on conflict, sought to identify poorly explained aspects and unknown information about the events that marked the region especially in the political context that, in presenting "Heroes" Squatters' Revolt of 1957 given the Walter Pecoits and Ivo Thomazoni reversed their participation in the uprising in political dividends at the local and regional level. Concluded by analyzing the monuments erected to commemorate the fiftieth anniversary of the Revolt of Squatters: the monument of the Seven Crosses Pranchita the monument made in tribute to the Pioneers in Capanema. It is observed that the monument is not something required by the settlers, but which is configured in a way in which the government relies for its construction to reap benefits themselves, used in his political milieu